3D FEM modeling and study of novel structure of magnetoelectric composites. (13th August 2019) - Do, Tuan Anh; Talleb, Hakeim; Gensbittel, Aurélie; Ren, Zhuoxiang
Abstract: This paper presents a 3D multiphysic modeling based on the coupling between the nonlinear discrete energy‐averaged model and the finite element method for the design optimization of magnetoelectric laminar structures. The model is applied to investigate the influence of the layer width on the output voltage and power performances while taking into account the magnetic losses due to the eddy currents.